Assessing effects of non‐native crayfish on mosquito survival. Issue 1 (28th September 2018) - Bucciarelli, Gary M.; Suh, Daniel; Lamb, Avery Davis; Roberts, Dave; Sharpton, Debra; Shaffer, H. Bradley; Fisher, Robert N.; Kats, Lee B.
Abstract: Introductions of non‐native predators often reduce biodiversity and affect natural predator–prey relationships and may increase the abundance of potential disease vectors (e.g., mosquitoes) indirectly through competition or predation cascades. The Santa Monica Mountains (California, U.S.A.), situated in a global biodiversity hotspot, is an area of conservation concern due to climate change, urbanization, and the introduction of non‐native species. We examined the effect of non‐native crayfish (Procambarus clarkii) on an existing native predator, dragonfly nymphs (Aeshna sp.), and their mosquito larvae (Anopheles sp.) prey. We used laboratory experiments to compare the predation efficiency of both predators, separately and together, and field data on counts of dragonfly nymphs and mosquito larvae sampled from 13 local streams. We predicted a lower predation efficiency of crayfish compared with native dragonfly nymphs and a reduced predation efficiency of dragonfly nymphs in the presence of crayfish. Dragonfly nymphs were an order of magnitude more efficient predators than crayfish, and dragonfly nymph predation efficiency was reduced in the presence of crayfish. Field count data showed that populations of dragonfly nymphs and mosquito larvae were strongly correlated with crayfish presence in streams, such that sites with crayfish tended to have fewer dragonfly nymphs and more mosquito larvae. Under natural conditions, it is likely that crayfish reduce the abundance of dragonfly nymphs and their predation efficiency and thereby, directly and indirectly, lead to higher mosquito populations and a loss of ecosystem services related to disease vector control. Abstract : Article impact statement : The efficiency of native predators to control potential disease vectors is diminished in the presence of non‐native predators. Abstract : Evaluación de los Efectos de un Cangrejo de Río Introducido sobre la Supervivencia de Mosquitos Resumen: La introducción de depredadores no nativos con frecuencia reduce la biodiversidad y afecta a las relaciones naturales entre presa y depredador, e incluso puede incrementar indirectamente la abundancia de vectores potenciales de enfermedades (p. ej.: mosquitos) por medio de la competencia o las cascadas de depredación. Las montañas de Santa Mónica (California, E.U.A.), situadas en un punto caliente de biodiversidad global, son un área de importancia para la conservación debido al cambio climático, la urbanización y la introducción de especies no nativas. Examinamos el efecto que tiene un cangrejo de río no nativo (Procambarus clarkii) sobre un depredador en existencia, las ninfas de libélula (Aeshna sp.), y sobre su presa: las larvas de mosquito (Anopheles sp.). Usamos experimentos de laboratorio para comparar la eficiencia de depredación de ambos depredadores, de manera separada y conjunta, y datos de campo sobre los conteos de ninfas de libélula y larvas de mosquito muestreadas en 13 riachuelos locales. Predijimos una eficiencia de depredación más baja de los cangrejos de río en comparación con las ninfas de libélula y una eficiencia de depredación reducida de las ninfas de libélula en presencia de los cangrejos de río. Las ninfas de libélula fueron depredadores un orden de magnitud más eficientes que los cangrejos de río, y la eficiencia de depredación de las ninfas de libélula estuvo reducida en la presencia de cangrejos de río. Los datos de conteo de campo mostraron que las poblaciones de ninfas de libélula y de larvas de mosquito tuvieron una fuerte correlación con la presencia de cangrejos de río en los riachuelos, de tal manera que los sitios con cangrejos de río tendieron a tener menos ninfas de libélula y más larvas de mosquito. Bajo condiciones naturales, es probable que los cangrejos de río reduzcan la abundancia de ninfas de libélula y su eficiencia de depredación, lo que resulta directa e indirectamente en poblaciones mayores de mosquitos y una pérdida de los servicios ambientales relacionados con el control de los vectores de enfermedades. 摘要: 引入外来捕食者常常会导致生物多样性丧失, 影响自然界捕食者‐猎物关系, 还可能通过竞争或营养级联效应间接增加潜在疾病传播媒介 (如蚊子) 的数量。圣莫尼卡山脉 (美国加利福尼亚州) 位于全球生物多样性热点地区, 因气候变化、城市化和外来物种的引入受到了保护关注。我们在这里分析了外来的小龙虾 (克氏原螯虾 Procambarus clarkii) 对原有本地捕食者蜻蜓若虫 (Aeshna sp.) 及其猎物蚊子幼虫 (Anopheles sp.) 的影响。我们通过实验室实验比较了这两种捕食者分别捕食和一起捕食的效率, 以及当地 13 条溪流中蜻蜓若虫和蚊子幼虫的数量。我们预测小龙虾的捕食效率低于本地的蜻蜓若虫, 而在有小龙虾存在的情况下, 蜻蜓若虫的捕食效率会下降。结果表明蜻蜓若虫的捕食效率比小龙虾高一个数量级, 且小龙虾存在时蜻蜓若虫的捕食效率的确会下降。野外统计的数据显示, 蜻蜓若虫和蚊子幼虫的种群数量与溪流中小龙虾的存在有很强的相关性, 有小龙虾的位点一般蜻蜓若虫较少、蚊子幼虫较多。在自然条件下, 小龙虾可能会引起蜻蜓若虫丰度下降, 捕食效率降低, 从而直接和间接地导致蚊子种群数量增加, 还导致与控制疾病传播媒介相关的生态系统服务功能丧失。【翻译: 胡怡思; 审校: 聂永刚】